APPLICATION OF ELECTROMAGNETICALLY INDUCED TRANSPARENCY (EIT) IN QUANTUM COMMUNICATION: A REVIEW - BABAYO, I.I.; LIMAN, A.M; AHMED, A.B (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
Electromagnetically induced transparency is a promising approach to implement quantum communication in quantum system. In this study, quantum coherence and interference in the excitation pathways of a three-level Λ atomic system leads to the formation of new states of matter (i.e. the dark state). This state decouples itself from the excitation beams leading to phenomena such as coherent population trapping (CPT), electromagnetically induced transparency (EIT). Taking into account quantum coherence and interference in an optically dense electromagneticallyinduced transparent medium, we investigate the non-destructive storage and retrieval of singlephoton quantum states in the dark state of this dense ensemble of gas phase medium. The storage and retrieval process is based on the intracavity electromagnetically induced transparency by which properties of a cavity filled with three-level Λ-type atoms are manipulated by an external control field. We demonstrate the peculiar case for the storage and retrieval of time-entangled periodic input pulses (a soliton train) in the dark state by adiabatic photon transfer under conditions of dynamical impedance matching. These multiplexed photon states are expected to allow sharing quantum information among many users, and are currently of very high demand for applications in longdistance and multiplexed quantum communication.